Using Electronic Services Provided by the Ministry of National Education as a Decision Support System: A Grounded Theory Study - Tayfun YÖRÜK; İlhan GÜNBAYI (Anı Publishing, 2022)
This study aims to put forward a theory for transforming electronic services provided by the Ministry of National Education and used in the schools into decision support systems within the scope of management information systems. This study is a theoretical study based on qualitative research methods using the interpretive paradigm. School administrators, psychological counselors, and guidance counselors make up the research group on the premise that it is voluntary.In the research, semi-structured interview forms were used as a data collection tool, the answers of the participants were recorded on a voice recorder, the recordings were analyzed and transcribed. Themes were obtained by applying open, axial, and selective coding, which are the steps of theory studies based on content analysis, using the NVivo 10.0 program on the obtained transcripts. In the light of these themes, a general model has been obtained explaining the transformation of management information systems into decision support systems. When the findings were examined, it was seen that the model obtained was similar to the open system theory. Accordingly, "Effective User Interface", "Collective Participation Based Monitoring System" and "Statistical Reporting", which correspond to the elements of open system theory, form the basis of the decision support system model to be applied in schools.